2018
DOI: 10.1017/inp.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Treatment Timing and Shrub Size on Chinese Privet (Ligustrum sinense) Control with Cut Stump Herbicide Treatments in the Southeastern United States

Abstract: Since its introduction to the United States in 1852, Chinese privet (Ligustrum sinenseLour.) has spread throughout the Southeast, invading many natural areas. Manual control by cutting or shredding is one of the most common strategies many land managers employ. However, rapid sprouting from the root collar and lateral roots commonly results in poor control. Cutting followed by either glyphosate or triclopyr application to the stumps is generally effective, but the efficacy of these herbicides in relation to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Even lower mortality was reported for woody weeds such as Ligustrum sinense Lour. (14% mortality) [ 27 ] and Ailanthus altissima (Mill.) Swingle (21% mortality) [ 28 ] if herbicide was not applied to the cut stump.…”
Section: Discussionmentioning
confidence: 99%
“…Even lower mortality was reported for woody weeds such as Ligustrum sinense Lour. (14% mortality) [ 27 ] and Ailanthus altissima (Mill.) Swingle (21% mortality) [ 28 ] if herbicide was not applied to the cut stump.…”
Section: Discussionmentioning
confidence: 99%
“…Triclopyr applied in high concentrations at the base of the plant in January, when seasonal defoliation is greatest, produced the highest mortality on Chinese privet in hardwood stands in Alabama (Enloe et al, 2016). A similar study found that lower concentrations of triclopyr or glyphosate are effective when applied as a cut stump treatment (Enloe et al, 2018). Triclopyr applied with similar methods on bottomland hardwood sites is an adequate herbicide for Chinese tallow as well, though other herbicides such as aminocyclopyrachlor may perform better (Enloe et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…The higher efficacy observed in the first run than in the second one, for the A + F treatment, can be attributed to the different periods in which the herbicide treatments were carried out: the first run in summer and the second run in spring. This behaviour is confirmed by the fact that woody species are generally better controlled when plants translocate the reserves to the roots, for winter storage, and not to the shoots as occurs in spring (DiTomaso and Kyser, 2007; Badalamenti et al ., 2015; Enloe et al ., 2018). Moreover, the carbohydrates in the roots are at their lowest level in mid‐summer and the plants, once cut, cannot rely on these reserves to produce new shoot as they generally do, thus their regenerative capacity is at its lowest in this period (Kays and Canham, 1991).…”
Section: Discussionmentioning
confidence: 99%